Foreign Policy Niche of Small States: The Problem of Choice (The Case of Baltic States) - V. A. Smirnov (Vestnik MGIMO-Universiteta)
The paper deals with the range of problems regarding the relation between decisions of political elite in small states and their striving for occupying a certain niche in external (foreign) political environment. The typology of such niches is proposed. The article deals with economic, military, political, and ideological dimensions of political elites' decisions in the Baltic states. The article makes the case of the following hypothesis: the exploitation of the "Russian threat" concept by political elites of the Baltic states is aimed at occupying a special niche within the Euro-Atlantic community. The narrow corridor for political maneuver imposed by strategic imperatives of NATO induces political elites of the Baltic states to attract attention of powerful states, which brings resources, finances and more prominent status. Inciting confrontation with Russia serves as a means for internal political consolidation, proving loyalty towards NATO, and contributes to individual careers of politicians with the EU institutions. The choice of 'conflict model' entails side-effects: slowdown of social and economic development in the long run. The following research inference is made: by means of conflict model which is being realized within external political niche ("gate-keeper" and "missionary" types) political elite of the Baltic states gain additional resources in the middle-term perspective. However, in the long term this political course generally reduces opportunities for political and economic development of small states. In theoretical and methodological dimension the research results confirm productivity of three-level analysis approach towards activity of political elite. The most general level of analysis deals with empire units of international relations which structure the environment for small states' elites actions. At the middle level it is possible scrutinize different varieties of external (foreign) political niches available to a certain small state. The third level of analysis deals with investigation of concrete economic, military, political and ideological decisions of political elite within a certain external (foreign) political niche.